Cover Image, Volume 23, Issue 9. Issue 9 (8th August 2021) - Lehmann, Vera; Tripyla, Afroditi; Herzig, David; Meier, Jasmin; Banholzer, Nicolas; Maritsch, Martin; Zehetner, Jörg; Giachino, Daniel; Nett, Philipp; Feuerriegel, Stefan; Wortmann, Felix; Bally, Lia
Abstract : The cover image is based on the Brief Report The impact of postbariatric hypoglycaemia on driving performance: A randomized, single‐blind, two‐period, crossover study in a driving simulator by Vera Lehmann et al., https://doi.org/10.1111/dom.14456 .